2010
DOI: 10.1007/s11606-010-1273-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient-centered Care: One Approach to Health Disparities Education

Abstract: BACKGROUNDPatient-centered care has been described as one approach to cultural competency education that could reduce racial and ethnic health disparities by preparing providers to deliver care that is respectful and responsive to the preferences of each patient. In order to evaluate the effectiveness of a curriculum in teaching patient-centered care (PCC) behaviors to medical students, we drew on the work of Kleinman, Eisenberg, and Good to develop a scale that could be embedded across cases in an objective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…With respect to the domain of 'focused interview,' we didn't achieve agreement (ICC À0.12). This finding is explained by the absence of any description of the 'focused interview' domain in all of those papers [26,27,33,34,45,49]. Full agreement was reached in only three of the included papers.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…With respect to the domain of 'focused interview,' we didn't achieve agreement (ICC À0.12). This finding is explained by the absence of any description of the 'focused interview' domain in all of those papers [26,27,33,34,45,49]. Full agreement was reached in only three of the included papers.…”
Section: Discussionmentioning
confidence: 97%
“…Four studies reported short and long case scenarios with obviously different durations [11,31,32,37], in contrast to nine studies which did not report station length at all [15,[47][48][49][50][51][52][53][54][55]. Sixteen studies reported references to validity and reliability studies of the assessment forms being used [11,15,24,26,27,30,39,40,[42][43][44][45][46][52][53][54], whilst six studies reported only validity ( [31,33,37,50,55], and twelve reported only reliability [25,28,32,[34][35][36]38,41,[47][48][49]51]. Two studies compared assessments of medical student CS across different institutions [4...…”
Section: Content Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(Chun 2010;Echeverri, Brookover et al 2010;Kamaka 2010;Wilkerson, Fung et al 2010;Crenshaw, Shewchuk et al 2011) These evolving tools will enrich the health care provider and enhance the relationship between diverse patients and the health care system. The next five years should be exciting as these tools, guides, and curricula emerge.…”
Section: Embedding Cultural Competence In Cancer Care Educationmentioning
confidence: 99%